Legal Study on the Oversight of Overloaded Motor Vehicles: Efforts to Protect Road Safety and Infrastructure - Imam Mukhlisin; Muhammad Hariri; Sainul (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2024)
The oversight of motor vehicles exceeding weight limits is critical in safeguarding road safety and protecting infrastructure from premature damage. Overloaded vehicles are a common issue, contributing significantly to accidents and accelerated road deterioration, which incurs high repair costs and disrupts public transport and logistics. This study examines the legal frameworks and regulatory practices aimed at controlling vehicle overloading in Indonesia. Utilizing a normative juridical approach, the research reviews pertinent laws, regulations, and real-world cases involving load limit violations to gain insights into the effectiveness of existing policies. Findings reveal that while stringent load regulations are in place, enforcement remains inconsistent due to various limitations, including outdated monitoring technology, insufficient human resources, and challenges in coordinating between regulatory agencies. The research identifies critical obstacles in the current oversight mechanisms, such as a lack of real-time data collection and limited roadside weighing facilities, which hinder comprehensive monitoring. Furthermore, penalties for overloading are often inadequate to deter repeat violations. Based on these findings, this study recommends a multi-faceted approach to strengthen vehicle load regulation enforcement. Suggested improvements include upgrading monitoring technology, such as installing automatic weigh-in-motion systems, increasing the frequency and coverage of roadside inspections, and implementing more severe penalties to enhance deterrence. Additionally, the study emphasizes the need for inter-agency coordination and public awareness campaigns to foster compliance among vehicle operators. Through these initiatives, Indonesia can better protect its roadways, ensuring both road safety for all users and the long-term sustainability of its infrastructure.